Alat Kendali Ph Air dan Nutrisi Sayur Selada Berbasis Arduino Dengan Sistem Nutrient Film Technique - Missi Hikmatyar; Rudi Hartono; Pandi Kurniawan (Sekolah Tinggi Teknologi Wastukancana, 2023)
Indonesia's population growth has increased every year which has an impact on the conversion of agricultural land into settlements. Hydroponics is a solution to the conversion of agricultural land. Hydroponics is a farming system without soil. In hydroponics, pH and nutrient levels are very important to keep plants growing properly. However, there are obstacles in the hydroponic farming system, namely in terms of controlling pH and nutrient levels which are still done manually. the result of not optimally controlling pH and nutrient levels in hydroponics will result in less optimal plant growth and even plant death. Therefore, we need a tool that can control pH and nutrient levels by using an Arduino microcontroller as a controller, a pH meter sensor to measure pH levels, and a TDS meter to measure nutrient levels. In this research, the hydroponic system used is the Nutrient Film Technique system, which is a hydroponic system that uses shallow water flow. This research was conducted in the hydroponic lab at the University of Perjuangan, Tasikmalaya, which still controls the levels of nutrients and the pH of the water used for hydroponic plants, which is still done manually. The results of this research are that the tool is designed to be able to maintain pH levels and nutrient levels for hydroponic lettuce plants with an error rate of 1.6% for pH sensors and 0.6% for TDS sensors which allows pH and nutrient levels for lettuce to be sufficient and stable.